IPTEKS AKUNTANSI PERTANGGUNGJAWABAN TERHADAP PEMERINTAH DAERAH DALAM TINGKAT PENILAIAN KINERJA PADA KELURAHAN SINGKIL II MANADO - Fernando, Ida Bagus Putu; Hunta, Aldi Andrew; Walandouw, Stanley Kho (Universitas Sam Ratulangi, 2018)
In a sub-district administration in singkil II, the implementation of accountability accounting is very influential and is needed in the current era, where the level of performance is very important to deal with any future problems. The average level of performance disclosure in this kelurahan is where accounting is needed, 4 of the 7 employees strongly agree on that, where the application of accounting accountability will be very helpful in the scope of the singkil II village office which has a very positive influence on all the people and especially the people in the kelurahan, and of course, behind all that there are leaders who are able to direct all of them into a village that is good in the eyes of the local government and the community.Keywords : responsibility accounting and performance assessment